Examining the social software characteristics and knowledge sharing behaviour among university students in Malaysia - Kaeomanee, Y. (Inderscience Publishers, 2014)
Knowledge sharing among students is an essential activity which can result in the improvement of student learning outcome. Recently, social software tools such as Facebook and content sharing sites are pervasively used by the students for sharing knowledge with peers. These tools have common characteristics which are informal setting, communication, network and community, and user generated content. This study attempts to examine the relationships between these characteristics and knowledge sharing behaviour of the students by integrating them into the theory of planned behaviour to develop a research framework and hypotheses. Questionnaire survey was collected from 322 students in five universities in Malaysia. The results of regression analysis showed that the aforementioned characteristics positively influenced attitude, subjective norm, and perceived behavioural control on knowledge sharing. Likewise, these three factors positively influenced the knowledge sharing intention which is the determinant of the actual knowledge sharing behaviour among the students.. Â© 2014 Inderscience Enterprises Ltd.